2018
DOI: 10.15407/ukrbotj75.05.457
|View full text |Cite
|
Sign up to set email alerts
|

Projected Kuialnytsky National Nature Park as a basis for optimization of the environment and sustainable development of the region

Abstract: Projected Kuialnytsky National Nature Park as a basis for optimization of the environment and sustainable development of the region. Ukr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Localized ecological systems are known to pass dramatically and irreversibly from one state to another when they forced to cross critical thresholds; it highlights the need to improve biological forecasting by identification of early warning signs of critical transitions at global as well as regional scales (Barnosky et al, 2012;Asif et al, 2018). Nowadays, the valley of the Liman Kuyalnik is in a state of ecological disaster (Dubyna et al, 2018b;Ennan et al, 2018). The established relationships in ecological differentiation of plant communities will be applied to further monitoring of the biodiversity state, preservation and possible restoration of vegetation types that are, or were, native for this unique territory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized ecological systems are known to pass dramatically and irreversibly from one state to another when they forced to cross critical thresholds; it highlights the need to improve biological forecasting by identification of early warning signs of critical transitions at global as well as regional scales (Barnosky et al, 2012;Asif et al, 2018). Nowadays, the valley of the Liman Kuyalnik is in a state of ecological disaster (Dubyna et al, 2018b;Ennan et al, 2018). The established relationships in ecological differentiation of plant communities will be applied to further monitoring of the biodiversity state, preservation and possible restoration of vegetation types that are, or were, native for this unique territory.…”
Section: Discussionmentioning
confidence: 99%
“…On the slopes of the estuary valley, large areas of native steppe vegetation have remained, and on the shore areas sites of halophytic vegetation are located. In 2016-2018, surveys of the liman valley vegetation were carried out, as a result of which a large variety of plant communities was detected and their syntaxonomic structure (Dubyna et al, 2017a(Dubyna et al, , 2018a and special features of territorial differentiation were found (Dubyna et al, 2017b(Dubyna et al, , 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…Аренами первинних сукцесій є значні за площами прилеглі території лиману, які звільнилися від води внаслідок його катастрофічного обміління та акумуляції на окремих ділянках делювіальних і алювіальних наносів [ENNAN et al, 2014, DUBYNA et al, 2018. На цих територіях формуються ряди угруповань, що змінюються і характеризуються низкою.…”
Section: результати досліджень та їх обговоренняunclassified
“…The estuary is well known for its healing mineralized waters and peloids. Its slopes of various steepness are represented by relatively well-preserved non-transformed areas covered by fescue-feather grass steppe communities, and flat areas are covered by saline-meadow and salt-marsh vegetation [28]. The vegetation development on them occurs under the influence of dynamic processes characterized by continuous variability.…”
Section: Introductionmentioning
confidence: 99%
“…Annual sea water releases from the Black Sea to the estuary since 2014 have not solved this problem. Primary, this affected the state of plant communities in plain areas [28]. Botanical surveys of the estuary valley started in the 19th century [32].…”
Section: Introductionmentioning
confidence: 99%